2012
DOI: 10.1007/s10549-012-2092-7
|View full text |Cite
|
Sign up to set email alerts
|

Rare oncogenic mutations of predictive markers for targeted therapy in triple-negative breast cancer

Abstract: Women with triple-negative breast cancer (TNBC) do not benefit from endocrine therapy or trastuzumab. Chemotherapy is the only systemic therapy currently available. To reduce the elevated risk of disease progression in these patients, better treatment options are needed, which are less toxic and more targeted to this patient population. We performed a comprehensive analysis of potential targetable genetic aberrations affecting the receptor tyrosine kinase/RAS/MAPK pathway, which are observed at higher frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
47
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 41 publications
6
47
1
Order By: Relevance
“…30,31 We also assessed EGFR amplification by the University of Colorado Cancer Center criteria and found that EGFR amplification was quite rare, being present in only 2% of cases, which is consistent with some previous studies. 10,19,25 However, EGFR high polysomy was found in 31% of cases, which is relatively higher than in previous studies. This result may be related to the heterogeneity of high polysomy in some cases, which will be discussed later.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…30,31 We also assessed EGFR amplification by the University of Colorado Cancer Center criteria and found that EGFR amplification was quite rare, being present in only 2% of cases, which is consistent with some previous studies. 10,19,25 However, EGFR high polysomy was found in 31% of cases, which is relatively higher than in previous studies. This result may be related to the heterogeneity of high polysomy in some cases, which will be discussed later.…”
Section: Discussioncontrasting
confidence: 70%
“…EGFR gene amplification and high polysomy were reported in up to 24% and 27% of triple-negative breast cancer, respectively (Table 8). 10,11,13,14,19,25 However, the frequency of EGFR gene amplification is quite variable, even though most studies used the same, University of Colorado Cancer Center criteria. 30,31 We also assessed EGFR amplification by the University of Colorado Cancer Center criteria and found that EGFR amplification was quite rare, being present in only 2% of cases, which is consistent with some previous studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…p53 mutations play an important role in tumorigenesis. It was reported that p53 is not highly expressed in breast cancer (Sjögren et al, 1996), but it has been found to be highly expressed in TNBC (Grob et al, 2012). Epidermal growth factor receptor (EGFR) can promote tumor cell migration and increase the invasiveness of tumor cells.…”
Section: Introductionmentioning
confidence: 99%